The early days of electrodermal activity - Sequeira, Henrique; Deren, Pascal; Maitte, Bernard (Anales de Psicología / Annals of Psychology, 2021)
This paper emphazises main steps of the discovery of one of the most salient autonomic markers of mind expressions, the electrodermal ac-tivity(EDA). The contribution of French and German schools of physiol-ogy, aimed by clinical needs and the desire to know further about physio-logical mechanisms, constitutesthe very early roots of such activity. In this frame, Féré and Tarchanoff, respectively a French and a Russiandiscover-ers, established the link between mind activity and the EDA on the one hand and laid the methodological foundations of modernutilisation of this neuromarker on the other hand. This heritage, associated with central neu-ral measures, is promised to an expanding future in neuropsychology, psy-chopathology, neurology, criminology and in cognitive and affective neu-roscience.